Multihazard Multisectoral Risk Communication Framework for Pakistan, 2021 - World Bank (Washington, DC : World Bank, 2022)
Pakistan remains susceptible to emergencies caused by a variety of natural hazards. There are two fundamental reasons for Pakistan’s high vulnerability. The first reason is increasingly high exposure due to rapid changes in the region such as unprecedented population growth, urbanization, deforestation, climate change, and rising human–animal proximity among others. The other reason for Pakistan’s high vulnerability, which is also critical to this particular endeavor, is its insufficient capacity for emergency response. Without disregarding the fact that the status of Pakistan’s capacity for risk communication has evolved since the JEE’s report in 2016 (especially considering the unprecedented focus on risk communication efforts during the COVID-19 pandemic), it is crucial to address the gaps identified to ensure Pakistan is prepared for the next public health mergency. This document provides the way forward for addressing those gaps. The document has two main components. The first main component of the document is an in-depth situation. analysis of the existing risk communication mechanism. The second is a framework for i) ensuring preparedness through institutionalization, and ii) activating campaigns during emergencies.